Tantangan Dalam Pengelolaan Bisnis Kewirausahaan - Rizky Auliani; Dinda Asri Ramadhani; Luthfiyyah Tasya; Mansur Keling (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The purpose of this research is to understand and know the challenges in managing an entrepreneurial business, as well as ways and strategies in entrepreneurship. This research is aimed at the public, such as the community, school children, and students. This type of research is qualitative using the literature library method which is a research approach carried out by collecting data, information, and relevant literature from written sources found in libraries or in the form of documents, articles, journals, books, reports, and other sources of information. The formulation of the problems contained in this study is how the challenges in managing entrepreneurial businesses and their methods and strategies. The results of this study are many challenges that must be faced by someone to be able to have a successful business, such as having to have a high intellectual about the business, having the capital to start a business and dare to compete with others. To be able to face this, an entrepreneur must be able to manage his business by planning, organizing, actually and controlling. In addition, an entrepreneur must have a strategy to survive to have a business, namely being able to manage business finances, always evaluating and willing to learn endlessly.